Independent Work of Students as a Factor of Increasing the Efficiency of the Educational Process - Urazbaeva Zulxumar Kuanishovna; Menlimuratova Sarbinaz Perdabayevna (Genius Publishing Group, 2021)
The article examines the role of students 'independent work, presents their components, considers the features of mental skills, presents the conditions for the effective organization of students' independent work.
Keywords: students; independent; awareness of the need for continuous self-improvement; individual activity of students; involvement in creative search